Domorganus gigas sp. n. (Nematoda) from Lake Baikal, Russia - Gagarin, Vladimir G.; Naumova, Tatyana V. (Zootaxa, 2015)
The genus Domorganus Goodey, 1947 includes nine valid species found in marine, freshwater and terrestrial habitats in Europe and Asia (Holovachov 2012). One species, D. acutus (Tsalolikhin, 1977) Lorenzen, 1981, is found in Lake Baikal, inhabiting the littoral zone (3 m depth) (Gagarin & Naumova, 2011).